Analysis Of The Role Of Traffic Units Against Offenders Of Speed Limit Violations That Cause Accidents - Ari Yoga Pasambuna (Universitas Negeri Gorontalo, 2019)
This study aims to find out how the analysis of the role of traffic units against criminal offenders of vehicle speed limit violations that cause accidents in Kotamobagu and what are the obstacles faced in minimizing traffic accidents due to speed limit violations in Kotamobagu and using this type of empirical legal research using qualitative approaches. This method of empirical legal research serves to see the law in reality in the community by collecting data and results with sources. The results of the research obtained the role of the Kotamobagu Resort Police Unit, namely preventive efforts (prevention) in the form of socialization and education to the community of road users and traffic engineering and repressive efforts (enforcement) in the form of Arrangements, Guarding, Escorts, and Patrols and enforcement against perpetrators of traffic accidents. Then the obstacles faced are the lack of facilities and infrastructure and lack of legal awareness in the community. Keywords: Satlantas; Speed Limit; Accident.